P-N ЎТИШЛИ ДИОДЛАРНИНГ ФЕРМИ КВАЗИ САТҲИ ВА ВОЛТЬ – АМПЕР ХАРАКТЕРИСТИКАСИГА МИКОТЎЛҚИН ТАЪСИРИ - Гулямов, Г.; Шаҳобиддинов, Б.Б.; Мажидова, Г.Н.; муҳандислик, Наманган; Қурбонова, Д.О. (SCIENCE and SOCIETY, 2022)
The quasi-levels of electrons and holes are studied in semiconductors in a strong microwave field. It is shown that these changes in the Fermi quasi-level strongly affect the current-voltage characteristic of a semiconductor diode with a p-n junction.